2023
DOI: 10.1002/smll.202303530
|View full text |Cite
|
Sign up to set email alerts
|

A Chiral Nanocomplex for Multitarget Therapy to Alleviate Neuropathology and Rescue Alzheimer's Cognitive Deficits

Huarong Tan,
Yuqi Huang,
Shuqing Dong
et al.

Abstract: Alzheimer's disease (AD) is a severe neurodegenerative condition characterized by inflammation, beta‐amyloid (Aβ) plaques, and neurodegeneration, which currently lack effective treatments. Chiral nanomaterials have emerged as a promising option for treating neurodegenerative disorders due to their high biocompatibility, strong sustained release ability, and specific enantiomer selectivity. The development of a stimulus‐responsive chiral nanomaterial, UiO‐66‐NH2@l‐MoS2 QDs@PA‐Ni (MSP‐U), for the treatment of AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Similarly, Tan et al demonstrated the potential of using chiral nanomaterials for treating AD. 304 To address neuronal loss in AD, L-molybdenum disulfide quantum dots (L-MoS 2 QDs) were used as the central component together with a carrier material and a surface coating. Under CPL NIR radiation, the L-MoS 2 QDs had a stronger effect at inducing neuronal differentiation of neural stem cells (NSCs) compared to the D configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Tan et al demonstrated the potential of using chiral nanomaterials for treating AD. 304 To address neuronal loss in AD, L-molybdenum disulfide quantum dots (L-MoS 2 QDs) were used as the central component together with a carrier material and a surface coating. Under CPL NIR radiation, the L-MoS 2 QDs had a stronger effect at inducing neuronal differentiation of neural stem cells (NSCs) compared to the D configuration.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic effects of MoS 2 on tumors and neurodegenerative diseases have been reported [ 50 53 ]. However, its application in peripheral nerve regeneration has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Chiral nanomaterials are well-known for their excellent chiroptical and chirality-dependent characteristics [ 32 ]. These properties have facilitated their widespread use in tissue engineering [ 33 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the intrinsic CuAlO 2 /ZnO p–n junction hardly meets the actual demand because the lower intrinsic mobility-concentration kinetic equilibrium makes achieving a high PCE difficult. Hence, effective modification is necessary, such as surface microstructure treatment or element doping. Transition-layer modification is a very feasible approach because it can increase carrier transportation with the appropriate Fermi level while increasing its mobility via carrier injection.…”
Section: Introductionmentioning
confidence: 99%